Nutrition intervention in bodybuilders in Limpopo Province, South Africa: anthropometric, serum lipid and micronutrient profiles - Sylven Masoga; Robert Schall; Peter Mphekgwana; Derik Coetzee; Elmine du Toit (Journal Coaching Education Sports, 2026)
Bodybuilders follow various diets, with some posing health risks. The study aimed to determine the baseline information on serum lipids and micronutrients, implement meal plans and evaluate the impact on these profiles of bodybuilders. An intervention study was conducted with 26 affiliated bodybuilders. The study was divided into baseline, intervention and post-intervention phases. In the baseline phase, anthropometry, serum lipid and certain micronutrient profiles were measured. The intervention phase was informed by baseline results, with athletes randomly assigned either to the experimental (n=14) or control (n=12) group. The experimental group received designed meal plans for three months. The post-intervention phase repeated measurements of the same variables in the baseline. Independent t-test and Wilcoxon test were used to determine the impact of meal plans between baseline and intervention variables. Total cholesterol (TC) and triglyceride (TG) serum levels were within acceptable standards, with a mean TC of 4.2 mmol/L for the experimental group and 3.8 mmol/L for the control group, and TG of 0.8 mmol/L for the experimental group and 0.7 mmol/L for the control group. High-density lipoprotein (HDL) and low-density lipoprotein (LDL) levels were within normal ranges for both groups. Dietary micronutrient intake and serum levels were mostly within the recommended daily allowance (RDA) and tolerable upper intake level (UL) in both groups. The nutrition intervention maintained bodybuilders' serum lipid and micronutrient profiles within acceptable standards.